A New Corpus of Roman Coins from England and Wales. An Overview of the Evidence and Analysis of the Data. - Henry, Richard (Britannia, 2024)
This paper considers a new corpus of 490,154 Roman coins (site finds) which have been recorded from England and Wales. The corpus provides British and regional means to aid in the preparation of coin reports in line with Historic England guidelines, along with spatial data providing new opportunities for research. The methods of data collection will be detailed and some of the possibilities this dataset can provide presented through a number of case studies. Through the consideration of applied numismatic analyses, the social distribution of the material and, crucially, the spatial distribution of Roman coinage, we can identify new trends and patterns. Case studies evaluating the fourth century will emphasise the changing importance of settlements in Roman Britain and identify those linked with the late Roman state. Furthermore, the retraction of coinage distributions in the second half of the fourth century will be explored. Building on the national and site type means explored within the paper, the full dataset has been made available in a range of forms on the Archaeology Data Service and in an interactive map developed by Maploom.